The Effect of Financial Literacy, Lifestyle and Personal Income on Consumptive Behavior in Millennial Generation in the Pandemic Era: Pengaruh Literasi Keuangan, Gaya Hidup dan Pendapatan Pribadi Terhadap Perilaku Konsumtif pada Generasi Milenial di Era Pandemi - Kiswoyo, Ayu Rahmawati; Kumalasari, Herlinda Maya (Indonesian Journal of Innovation Studies, 2022)
This study aims to describe and find out about the influence of Financial Literacy, Life Style and Personal Income on Consumptive Behavior in Millennial Generation In The Pandemic Era. This research method is a type of quantitative research with hypothesis testing. The sample used was 210 students from the 2018 batch at Muhammadiyah University of Sidoarjo. The data collection technique was carried out using a questionnaire distributed online using a google form. The data analysis technique in this study used multiple linear regression through the SPSS Statistics version 24 program. The results of this study indicate that, Financial Literacy has an effect on Consumptive Behavior, Life Style has an effect on Consumptive Behavior, Personal Income has an effect on Consumptive Behavior and Financial Literacy, Life Style and Personal Income have a simultaneous effect on Consumptive Behavior.